2007
DOI: 10.1159/000102146
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Cardiovascular Damage

Abstract: Acute coronary syndromes (ACS) are due to the rupture or erosion of atheromatous plaques. This produces, depending on plaque size, vascular anatomy and degree of collateral circulation, progressive tissue ischaemia which may progress to cardiomyocyte necrosis. This may then result in cardiac remodelling. Serum biomarkers are available which can be used for diagnosis of all of these stages. Markers to detect myocardial ischaemia at the pre-infarction stage are potentially the most interesting but also the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 236 publications
0
21
1
1
Order By: Relevance
“…It has been previously validated in a murine model of experimental autoimmune myocarditis, and demonstrates greater utility than creatine kinase or anti-cardiac myosin antibodies [45], [46], [47], [48], [49]. Increased serum cTnI levels positively correlate with increased levels of histopathological changes in the myocardium, and serum markers are a facile means of tracking cardiac injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously validated in a murine model of experimental autoimmune myocarditis, and demonstrates greater utility than creatine kinase or anti-cardiac myosin antibodies [45], [46], [47], [48], [49]. Increased serum cTnI levels positively correlate with increased levels of histopathological changes in the myocardium, and serum markers are a facile means of tracking cardiac injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical pacing has not been used in the study because it is reported to release norepinephrine (Nayler et al, 1985). Infarct size in the present study is assessed macroscopically because a good correlation has been noted between infarct size measured macroscopically and microscopically (Banka et al, 1981;Collinson and Gaze, 2007). The duration of 30 min ischemia and 120 min reperfusion employed in this study has been reported to produce apoptosis (Maulik et al, 1999).…”
Section: Discussionmentioning
confidence: 87%
“…It might be that, in obese adolescents, the excess in fat mass causes MRproADM overproduction, drowning out its age-related changes. The higher MR-proADM plasma levels found in obese adolescents are unlikely to be attributable to cardiovascular alterations, since both BNP and NTproBNP, considered sensitive biomarkers of cardiac dysfunction used in the diagnostic and prognostic staging of chronic and acute cardiac conditions across all ages [33], resulted in normal range and comparable between obese and normalweight adolescents. The pathophysiological role of ADM secreted by adipose tissue in obese subjects is still speculative.…”
Section: Discussionmentioning
confidence: 98%